Exploring the implementation of the TIME Home Learning programme and learning trajectories of 5- to 7-year-olds: What difference did TIME make? - von Blottnitz, Magali (Wordworks, Cape Town, 2025)
This brief analyses a range of evidence collected during the TIME longitudinal study (2022-2023) and discusses to what extent the evidence supports the claim of impact of the TIME Home Learning programme on the child’s learning trajectories. First, a thematic analysis of interview data from caregivers and teachers surfaces the programme’s impact chain, whereby strengthened relationships support a growth in children’s soft skills, which in turn accelerate the children’s learning. The same mechanisms are then studied through the review of three case studies. Finally, a review of broader sample data attempts to interrogate how to generalise the case study findings. The brief concludes that programmes like TIME provide an opportunity for average families, where children stand at the edge of risk and possibility, to boost the children’s learning trajectories and help them stay on track.
TIME Learning Brief 7
This is the seventh and final in a series of TIME learning briefs. By weaving together the themes from previous briefs, this brief explores connections between the quality of implementation of TIME in the homes, the participating children’s personal development and their learning trajectories. In particular, it addresses the observations of caregivers and teachers about the effect of TIME on children and; through the study of three individual children’s stories, the mechanisms through which TIME impacts children’s academic achievement.
Keywords: Foundation phase; home-learning; caregiver involvement; parental involvement; parents; early literacy; early mathematics; numeracy; TIME; South Africa; Grade R; Grade 1; reading; writing; counting; WELA; MELA; Wordworks; RED INK